NEOSPOROSIS EN BOVINOS LECHEROS EN DOS DISTRITOS DE LA PROVINCIA DE CHACHAPOYAS - Quevedo V., Janios (2003)
Neosporosis is a parasitic disease caused by the protozoan Neospora caninum, and is associated with high rates of abortion in cattle throughout the world. The aim of the study was to determinate the seroprevalence of N. caninum in dairy cattle reared in the districts of Molinopampa and Leymebamba, Chachapoyas province, Amazonas. The study was carried out in 2002 using 265 serum samples from cows older than 2 years old that belonged to 24 dairy herds. Samples were tested to detect antibodies against N. caninum using the IFAT test. The 40.4 ± 5.0% (107/265) of the samples had antibodies in 1:200 dilution. All sampled herds had at least one seropositive animal. The prevalence of the parasite was similar in both districts and similar to described in herds from other dairy areas in the country.